ILLEGAL ENROACHMENT IN THE COMMUNITY OF WATU ATA NATURAL RESERVE AREA, BAJAWA DISTRICT, NGADA DISTRICT - Roswina Junianti Ule; Arfita Rahmawati; Bella Theo Tomi Pamungkas (GeoEco, 2025)
The large number of people who occupy, control, and cultivate areas in conservation forest areas illegally, for subsistence or commercial purposes without paying attention to statutory regulations, is a problem in the Watu Ata Nature Reserve. Even though the government already has a social forestry program that collaborates with communities regarding forest management. This research aims to determine the location, and factors that influence the occurrence of illegal land use in the Watu Ata nature reserve area, Bajawa District, Ngada Regency. The sample used a spatial sample, namely locations of illegal land use and 60 squatter communities. This research method uses multiple regression analysis and spatial interpolation. The results of this research show that economic factors, social factors, and environmental factors influence the impact of encroachment. The low level of illegal occupation is in Langagedha Village and the high level is in Wawowae Village and Jawameze Village. Recommendations from this research are that Wawowae Village, with an area of 132.77 hectares in Wawowae Village can be used as a location for social forestry.